Lycopene Improves In Vitro Development of Porcine Embryos by Reducing Oxidative Stress and Apoptosis - Hyo-Gu Kang; Sanghoon Lee; Pil-Soo Jeong; Min Ju Kim; Soo-Hyun Park; Ye Eun Joo; Sung Hyun Park; Bong-Seok Song; Sun-Uk Kim; Min Kyu Kim; Bo-Woong Sim (MDPI AG, 2021)
In vitro culture (IVC) for porcine embryo development is inferior compared to in vivo development because oxidative stress can be induced by the production of excessive reactive oxygen species (ROS) under high oxygen tension in the in vitro environment. To overcome this problem, we investigated the effect of lycopene, an antioxidant carotenoid, on developmental competence and the mechanisms involved in mitochondria-dependent apoptosis pathways in porcine embryos. In vitro fertilized (IVF) embryos were cultured in IVC medium supplemented with 0, 0.02, 0.05, 0.1, or 0.2 μM lycopene. The results indicate that 0.1 μM lycopene significantly increased the rate of blastocyst formation and the total cell numbers, including trophectoderm cell numbers, on Day In terms of mitochondria-dependent apoptosis, IVF embryos treated with 0.1 μM lycopene exhibited significantly decreased levels of ROS, increased mitochondrial membrane potential, and decreased expression of cytochrome c on Days 2 and Furthermore, 0.1 μM lycopene significantly decreased the number and percentage of caspase 3-positive and apoptotic cells in Day-6 blastocysts. In addition, Day-2 embryos and Day-6 blastocysts treated with 0.1 μM lycopene showed significantly reduced mRNA expression related to antioxidant enzymes (SOD1, SOD2, CATALASE) and apoptosis (BAX/BCL2L1 ratio). These results indicate that lycopene supplementation during the entire period of IVC enhanced embryonic development in pigs by regulating oxidative stress and mitochondria-dependent apoptosis.